Has the Janani Suraksha Yojana (a conditional maternity benefit transfer scheme) succeeded in reducing the economic burden of maternity in rural India? Evidence from the Varanasi district of Uttar Pradesh - Saradiya Mukherjee; Aditya Singh (SAGE Publishing, 2018)
Background. One of the constraints in the utilisation of maternal healthcare in India is the out-of-pocket expenditure. To improve the utilisation and to reduce the out-of-pocket expenditure, India launched a cash incentive scheme, Janani Suraksha Yojana (JSY), which provides monetary incentive to the mothers delivering in public facility. However, no study has yet examined the extent to which the JSY payments reduce the maternal healthcare induced catastrophic out-of-pocket expenditure burden of the households. This paper therefore attempts to examine the extent to which the JSY reduces the catastrophic expenditure estimate household expenditure on maternity, i.e., all direct and indirect expenditure. Materials and methods. The study used data on 396 mothers collected through a primary survey conducted in the rural areas of the Varanasi district of Uttar Pradesh state in 2013-2014. The degree and variation in the catastrophic impact of households' maternity spending was computed as share of out-of-pocket payment in total household income in relation to specific thresholds, across socioeconomic categories. Logistic regression was used to understand the determinants of catastrophic expenditure and whether the JSY has any role in influencing the expenditure pattern. Results. Results revealed that the JSY beneficiaries on an average spent about 8.3% of their Annual Household Consumption Expenditure on maternity care. The JSY reimbursement could reduce this share only by 2.1%. The study found that the expenditure on antenatal and postnatal care made up a significant part of the direct medical expenditure on maternity among the JSY beneficiaries. The indirect or non-medical expenditure was about four times higher than the direct expenditure on maternity services. The out-of-pocket expenditure across income quintiles was found to be regressive i.e. the poor paid a greater proportion of their income towards maternity care than the rich. Results also showed that the JSY reimbursement helped only about 8% households to escape from suffering catastrophic burden due to maternity payments. Conclusions. It can be concluded that the JSY appeared to have achieved only a limited success in reducing the economic burden due to maternity. To reduce the catastrophic burden, policy makers should consider increasing the JSY reimbursement to cover not only antenatal and postnatal services but also non-medical expenditure due to maternity. The government should also take appropriate measures to curb non-medical or indirect expenditure in public health facilities.